Efektivitas Media Edukasi Booklet Pola Asuh Ibu Terhadap Pengetahuan dan Sikap Ibu Balita Stunting di Wilayah Kerja UPTD Puskesmas DTP Singah Mulo - Raodah; Andi Pratama Putra, (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2024)
The results of the integration of the Indonesian Toddler Nutrition Status Study (SSGBI) and the National Socioeconomic Survey (Susenas) in March 2019 showed that the prevalence of stunting in Indonesia was 27.7% and the prevalence of stunting in Aceh Province was 34.18%. This study aims to determine the effect of booklet educational media on the knowledge and attitudes of stunting toddler mothers with quantitative research, namely a quasi-experimental design with a research design using one-group pretest-posttest design with a sample size of 60 mothers with stunting toddlers. This research was conducted in june-july 2024. The instrument used in this study is questionnaries were given before and after using booklet media. Statistical test using the Wilcoxon test. The results of the Wilcoxon test showed the effect of booklet media education on mother's knowledge (p value 0.00) and on the attitude of stunting mothers (p value 0.00). In conclusion, booklet educational media has an effect on increasing the knowledge and attitudes of stunting toddler mothers